Relationship Between Sitting Duration And Complaints Of Low Back Pain In Online Ojek Drivers In Bangkalan - Annida Diana Islami; Ali Multazam; Safun Rahmanto (Jurnal EduHealth, 2024)
Low Back Pain (LBP) or commonly called low back pain is a complaint of pain that can be felt in the spine of the spinal region (lower back). The duration of sitting is the period of time used to perform the activity of resting the body by resting on the buttocks while working. The purpose of this study was to determine the relationship between sitting duration and complaints of low back pain in online motorcycle taxi drivers in Bangkalan. Methods: This study used quantitative research with a cross-sectional approach. Sampling in this study was based on purposive sampling technique with a total sample of 74 respondents. Data taken using the Roland-Morris Disability Questionnaire (RMDQ). Results: in this study using the spearman rank test and obtained a significance value of 0.000 (<0.005). Conclusion: there is a relationship between sitting duration and complaints of low back pain in online motorcycle taxi drivers in Bangkalan.